Association between SOCS3 hypermethylation and HBV-related hepatocellular carcinoma and effect of sex and age: A meta-analysis. Issue 43 (29th October 2021) - Zheng, Hairu; Yan, Yanggang; Cheng, Jiajia; Yu, Shuyong; Wang, Yong
Abstract: Background: Suppressor 3 of cytokine signaling (SOCS3) hypermethylation has been reported to participate in hepatocellular carcinoma (HCC) development and progression, but conflicting results were published. This study aimed to analyze the clinical effects of SOCS3 hypermethylation in HCC and the effects of sex and age on SOCS3 hypermethylation in HCC. Methods: Databases were searched for relevant case-control and cohort studies on SOCS3 hypermethylation in HBV-related HCC. In vitro and in vivo studies and studies of patients with serious comorbidities were excluded. Review Manager 5.2 was used to estimate the effects of the results among the selected studies. Forest plots, sensitivity analysis, and bias analysis for the included studies were also conducted. Results: Finally, 8 relevant studies met the inclusion criteria. A significant difference in SOCS3 hypermethylation in HCC was found between tumor and nontumor groups (the odds ratio [OR] = 2.01, 95% confidence interval [CI]: 1.48–2.73, P  < .00001; P for heterogeneity = .39, I 2  = 5%). The meta-analysis suggested no significant difference in the effect of sex (OR = 1.00, 95% CI: 0.76–1.31, P  = .76; P for heterogeneity = .44, I 2  = 0%) and age on SOCS3 hypermethylation in HCC (OR = 1.11, 100% CI: 0.78–1.29, P  = .03; P for heterogeneity = .14, I 2  = 36%). Limited publication bias was observed in this study. Conclusion: SOCS3 hypermethylation is associated with HBV-related HCC. Sex and age do not affect the association between SOCS3 hypermethylation and HCC. SOCS3 might be a treatment target for HCC.